2013
DOI: 10.4049/jimmunol.1301559
|View full text |Cite
|
Sign up to set email alerts
|

STAT-3 Activation by Differential Cytokines Is Critical for Human In Vivo–Generated Plasma Cell Survival and Ig Secretion

Abstract: Maturation and survival of plasma cells (PCs) depends on extrinsic factors provided in specialized niches. In addition, B lymphocyte differentiation into PCs requires the activation of the JAK–STAT-3 pathway. However, whether STAT-3 is needed only during the transition of B lymphocytes to PC, or it is also involved in the survival and function of PCs at different stages of maturation, has not been unequivocally clarified. This study analyzes the effect of IL-10, IL-21, and IL-6 on human in vivo–generated PCs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 51 publications
7
51
0
Order By: Relevance
“…IL-10-mediated increases in B cell survival, proliferation, terminal differentiation, and Ab secretion were reported in a multitude of studies in mammals (79)(80)(81). Therefore, in the last part of this study we focused on the regulatory activities of carp Il10 on B lymphocytes (IgM + ), in particular on the ability of Il10 to regulate B cell proliferation, differentiation, and Ab production.…”
Section: Discussionmentioning
confidence: 98%
“…IL-10-mediated increases in B cell survival, proliferation, terminal differentiation, and Ab secretion were reported in a multitude of studies in mammals (79)(80)(81). Therefore, in the last part of this study we focused on the regulatory activities of carp Il10 on B lymphocytes (IgM + ), in particular on the ability of Il10 to regulate B cell proliferation, differentiation, and Ab production.…”
Section: Discussionmentioning
confidence: 98%
“…Peripheral blood (PB) samples were obtained from healthy donors 6 d after receiving a conventional booster immunization against tetanusdiphtheria toxoids and acellular pertussis (Boostrix; GlaxoSmithKline Biologicals SA, Rixensart, Belgium) (23). BM specimens showing no abnormalities were collected from discarded BM aspirates obtained for diagnostic purposes.…”
Section: Human Samplesmentioning
confidence: 99%
“…It has been previously demonstrated that these PCs express functional CXCR4 (13,14,22), the receptor for CXCL12, a prerequisite for homing in BM PC niches (11,12). In addition, they have the capacity of responding to cytokines such as IL-6 and others present in the long-living PC niches (23). All of these features combined with its transient and temporary relation with serum Ab appearance have led to the belief that the blood Aginduced PC pool contains the precursors of long-living BM PCs specific for every Ag (11,12).…”
mentioning
confidence: 99%
“…Beside its role in inducing IL-10 production 42,43 in B cells, IL-21 produced by human follicular helper T cells and CD4 Th17 cells is also critical for human plasmablast differentiation. [47][48][49][50] Elevated levels of IL-21 51 and IL-21-producing cells 52 have been found in human cGVHD and a deleterious role of IL-21 has been demonstrated in mouse models of cGVHD. 25,52 Accordingly, we found relatively high basal levels of phosphorylated STAT3 as well as increased circulating plasmablasts in cGVHD patients in our study.…”
mentioning
confidence: 99%